CATCHING UP WITH BUILDING INFORMATION MODELING: CHALLENGES AND OPPORTUNITIES FOR QUANTITY SURVEYORS - Zainon, Nurshuhada; Mohd-Rahim, Faizul Azli; Aziz, Nur Mardhiyah; Kamaruzzaman, Syahrul Nizam; Puidin, Sapturinah (Journal of Surveying, Construction and Property, 2018)
Building Information Modeling (BIM) is gaining a momentum within the construction industry in Malaysia, and worldwide. The 5-dimensional (5D) of BIM has sparked a new way of working in Quantity Surveying practice, transforming the traditional functions of a Quantity Surveyor (QS). This paper highlights the potential use of BIM in Quantity Surveying practices, subsequently discusses the challenges and opportunities gained from BIM advancement in QS profession, especially in Malaysia. Through an extensive literature review and content validation process, the utilization of BIM technology in Quantity Surveying practices works wonder in saving the time of QS have to spend on cost analysis and enhances accuracy; it does not become a threat to the profession, but BIM provides opportunities to direct QS talents towards being more efficient. The outcome of this paper should direct the QS to be BIM-ready, further could become a guide for Quantity Surveying companies’ planning in enhancing skills and QS competencies in utilizing BIM hence reinforcing QS role amongst the construction professional discipline.